Distance education environments and emerging software systems new technologies - Jin, Q. (Qun), 1962-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book focuses on the discussions of computational methods, algorithms implemented prototype systems, and applications of open and distance learning"--Provided by publisher.
12. The construction of an ontology-based ubiquitous learning grid / Ching-Jung Liao, Chien-Chih Chou and Jin-Tan David Yang -- 13. A rule-based system for test quality improvement / Gennaro Costagliola and Vittorio Fuccella -- 14. An understanding information management system for a real-time interactive distance education environment / Aiguo He -- 15. The effects of communicative genres on intra-group conflict in virtual student teams / Jung-Lung Hsu and Huey-Wen Chou -- 16. Effect of teaching using whole brain instruction on accounting learning / Li-Tze Lee and Jason C. Hung -- 17. Using S-P chart and bloom taxonomy to develop intelligent formative assessment tool / Wen-Chih Chang, Hsuan-Che Yang, Timothy K. Shih and Louis R. Chao -- 18. A study of English mobile learning applications at National Chengchi University / Pei-Chun Che, Han-Yi Lin, Hung-Chin Jang, Yao-Nan Lien and Tzu-Chieh Tsai -- 19. E-learning practice and experience at Waseda E-School: Japan's first undergraduate degree-awarding online program / Shoji Nishimura, Douglass J. Scott and Shogo Kato.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed June 16, 2011).
Keywords: Distance education -- Computer-assisted instruction; Distance education -- Technological innovations; Automatic assessment methods; Effective and efficient authoring systems; Individualized distance learning; Intelligent tutoring; Mobile systems; Multimedia streaming technology; Multimedia synchronization controls; New network infrastructures; Quality-of-service issues; Real-time protocols; Electronic books